Kepemimpinan dan Kinerja Personel Polri di Polres X - Monica Mega Maharani; Nuri Herachwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This article aims to explain the influence of leadership on the performance of police at the X Police. The role of leadership is a determinant of the success of community service delivery. So to realize a good police service institution, it is necessary to improve the professionalism and performance of the police personnel. so that the quality of service to the community also increases. The research used quantitative approach with associative type. The population of this study is all Polri personnel in the implementing elements of the Criminal Investigation Unit (Satreskrim), Traffic Unit (Satlantas), and the Samapta Bhayangkara Unit (Sabhara) at the X Police with 222 members. Data collection techniques used two sources of data, namely primary data including questionnaires and interviews, and secondary data including documentation and literature study. Hypothesis testing was carried out using Spearman Rank correlation analysis, besides that, validity and reliability tests were carried out using SPSS 25. Based on the results of statistical tests, it was shown that there was a significant influence between leadership and performance. Spearman's Rank test results in rs x.y = 0.627. The t-significance test resulted in a count of 2.259. This calculated number is greater than the number in table B, which is 2,047 at an alpha of 0.005. Decisions that can be taken based on the results of the analysis of this study are to reject H0 and accept Ha, meaning that there is a significant influence between leadership and the performance of the police at the X Police